Takyif fiqhi and its application to modern contracts: a case study of the central provident fund nomination in Singapore - El-Mesawi, Mohamed El-Tahir; Leman, Mohammad Rizhan (IIUM Press, International Islamic University Malaysia, 2018)
The term takyif fiqhi stands for one crucial concept in Islamic jurisprudence and refers to one of the important steps in the process of formulating fatwÉ. It basically revolves around the categorization of particular issues under the appropriate rules and precedents established in Islamic juristic thought. The present article attempts to examine the concept of takyif fiqhi in a comprehensive manner in terms of its meaning, authority, types, importance, and governing criteria as can be gleaned from the works of Shari'ah scholars. This is then followed by an exploration of its application to modern contracts, taking as a case study the Central Provident Fund Nomination in Singapore. The article concludes with the view that the Central Provident Fund Nomination, in terms of its essential characteristics and objective, resembles the Islamic will contract as discussed in books of Islamic Jurisprudence. ********************************************************